Almond oil improves the levels of some trace elements and antioxidant status in mice exposed to oxidative stress - Amer Alasadi; Husam Al-Hraishawi; Haider Humaish (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate the concentrations of some trace elements and the antioxidant status in male mice exposed to oxidative stress by carbon tetrachloride and then treated by either almond oil or vitamin C. Methods: The animal study was conducted in January 2020 at the College of Nursing of the University of Thi-Qar and the Kut Technical Institute, Middle Technical University, Baghdad, Iraq, and comprised adult male mice. They were divided randomly into four equal groups and treated for 21 days. Mice in group I received sunflower oil 1ml per mice, mice in group II were injected 0.3% carbon tetrachloride intraperitonially, mice in group III received 0.3% carbon tetrachloride plus oral intubation of vitamin C 300mg/kg body weight daily, and mice in group IV were intubated with 2.26g/kg body weight of almond oil plus 0.3% carbon tetrachloride daily. Serum and liver homogenate were used to measure the levels of trace elements and the antioxidant status. Data was analysed using SPSS version 20. Results: There were 24 mice; 6(25%) in each on the 4 groups. Mice in group II showed a significant decrease in zinc, magnesium and phosphorus levels, and significant elevation in calcium levels (p<0.05). Mice in groups III and IV showed a significant difference in trace elements compared to group II (p<0.05). Almond oil enhanced the antioxidant status and was more active than vitamin C (p<0.05). Conclusions: Almond oil was found to have beneficial and pharmacological effects against oxidative stress. Keywords: Carbon tetrachloride, Antioxidants, Prunus dulcis, Ascorbic acid, Phosphorus, Fatty liver, Zinc, Vitamins, Intubation, Intratracheal.